Process Evaluation of Auditable Pharmaceutical Transaction Service in Seka primary Hospital, Jimma Zone, South West Ethiopia - Daniel Aboma; Yisalemush Assefa; Matebe Gezahegn (Journal of Women's Reproductive Health, 2020)
Background A well-functioning drug supply management is the corner stone for any meaningful health service. However, Pharmaceutical supply systems in many developing countries have severe problems, including inefficient selection, procurement and use of drugs. The magnitude and extent of the problem is huge and chronic in the Ethiopian health care system for a long time. Objective To evaluate auditable pharmaceutical transaction service process in Seka primary hospital, Jimma zone south west Ethiopia. Evaluation Methodology Case study design involving both quantitative and qualitative methods was conducted in Seka primary hospital. The focus of this evaluation was on the process of Auditable pharmaceutical transaction service. The evaluation was focused on process part of the program with dimensions; availability, compliance and client satisfaction in the dimension of accommodation. Resource inventory, document review; key informant interviews and observations were conducted. Client satisfaction was assessed through exit interview; with sample size of 326. The qualitative data was analyzed manually using thematic analysis and quantitative data were analyzed by using SPSS version 23 software. Results In Seka primary hospital, percentage availability of the 32 selected Key medicinewas 10.7(82.0%) and there were no expired drugs found on their shelves. The availability of 17 of the required 20(85%) professionals was adequate according the Auditable pharmaceutical transaction service. The average lead time was found to be less than five days. The average counselling and dispensing time were 5:43 minutes and 1:17 minutes, respectively. The average number of drugs per prescription was 2.0. The 1154(97.9%) of drugs prescribed by generic name and 1175(99.7%) of prescribed drugs on Essential Drug List indicates prescribers ‘adherence to facility specific List. Conclusion This evaluation revealed that (based on the pre-set judgment criteria) the achievement of the Auditable pharmaceutical transaction service in Seka primary Hospital was GOOD 82.6 % (achieved 355.2 of 430 weight given), i.e. even though it is Good achievement ,there are areas that needs improvement. Areas for improvement identified were: Pre- and in-service training for all health workers involved in store room and dispensary to improve on the medium counselling time, poor record keeping and the extremely poor labelingof drugs which this all improve the overall client satisfaction.
Keywords: APTS